Breeding Biology, Chronology, and Reproductive Success of the European Serin (Serinus serinus) at Moulouya High Plain (Morocco) - Mansouri, Ismail; Squalli, Wafae; Dakki, Mohamed; Assouguem, Amine; El Agy, Abdelbari; El Hassani, Abderahim; Belarbi, Chaimae; Dbiba, Youssef; Kouali, Hassnae; El Ghadraoui, Lahsen (International Journal of Zoology, 2021)
The European serin (Serinus serinus) is one of the best examples of a species in the western Palaearctic that has expanded its distribution ranges in current periods. However, the breeding features of serin are not well known and were restricted for some localities, as well as there have not been any deep and comparable studies on its mortality and menacing factors. This study investigates breeding biology, including breeding chronology, nesting strategies, and reproductive success of the European serin in farmland and woodland habitats at Moulouya high plain (Morocco), during 2016. Results showed that, at high-altitude breeding habitats, the European serin started breeding activity lately by 25 April (construction of the first nest) and continued until 19 July (last fledging date). Moreover, most nests (96.42%) were found in farmlands, mainly in apple orchards. Two broods were recorded between April-May and June-July, and the clutch size was an average of 3.04 ± 0.13 eggs/nest. For reproductive success, among the 65 examined nests, 73.84% were active during the nest construction phase and 87.42% of eggs have succeeded during the incubation phase. Reproductive success was higher (93.83%) during fledging. Clutches were failed due to predation (15.9%), nest desertion (14.35%), and destruction of nests (8.88%). Finally, our study highlights that the European serin breeds in high-altitude zones with late and shorter breeding seasons, which might allow this bird to avoid high lands’ vigorous climate conditions and their eﬀect on breeding success.